Oyster Demographics in Harvested Reefs vs. No-Take Reserves: Implications for Larval Spillover and Restoration Success - Peters, Jason W.; Eggleston, David B.; Puckett, Brandon J.; Theuerkauf, Seth J. (Frontiers in Marine Science, 2017)
Fishery species that reside in no-take, marine reserves often show striking increases in size and abundance relative to harvested areas, with the potential for larval spillover to harvested populations. The benefits of spillover, however, may not be realized if the populations or habitats outside of reserves are too degraded. We quantified oyster population density and demographics such as recruitment, growth, mortality, and potential larval output as a function of two types of oyster management strategies in Pamlico Sound, North Carolina, USA: (1) natural reefs + harvested and (2) restored reefs + harvested. We compared these data to demographic data collected as a function of a third type of management strategy, (3) restored reefs + protected from harvest. Mean oyster recruitment was ~12 times higher in restored + harvested reefs than in natural + harvested reefs. Mean total oyster density was ~8- to 72-times higher in restored + protected reefs than in restored + harvested or natural + harvested reefs, respectively. Moreover, harvested reefs exhibited truncated size structure, and few or no individuals greater than legal size (75 mm), whereas protected reefs typically had a polymodal size structure, including many large individuals. We estimate that restored + protected reefs have ~4 to 700 times greater potential larval output m-2 than restored + harvested or natural + harvested reefs, respectively. After accounting for total sound-wide areal coverage of each reef type, total potential larval output from restored + protected reefs was ~6 times greater than that from natural + harvested and restored + harvested reefs. Marine reserves can potentially subsidize harvested populations via larval spillover, however, in the case of oyster reefs in Pamlico Sound, the relatively degraded conditions of natural reefs (e.g., low vertical relief, low shell volume per square meter) may not provide much in the way of suitable settlement substrate to realize the benefits of larval spillover from reserves. Restoration of oyster reefs, even with a thin veneer of substrate, may improve settlement substrate to increase the benefits of larval spillover from reserves.